Технології розробки програмного забезпечення - Вискребець, Д. О. (ХНУРЕ, 2019)
This work gives an overview over the basic concepts of data and sensor fusion. Today sensors are used in vast majority of systems all over the world to recognize and analyze objects. But sensor systems have range of drawbacks that reduce their efficiency. Sensor fusion offers a great opportunity to overcome physical limitations of sensing systems. We discuss several sensor fusion algorithms such as Kalman Filter, inference methods and their application in everyday life. Their application in intelligent transport systems, real-time systems and unmanned aerial vehicles